2â,4â-Dihidroksi-3â,5â,6â-Trimetoksi Calkon suatu Senyawa Antitumor dari Kulit Batang Tumbuhan Cryptocarya costata (Lauraceae) - Hanapi Usman; Euis Holisotan Hakim; Sjamsul Arifin Achmad; Tjodi Harlim; Muhammad N. Jalaluddin; Yana Maolana Syah; Lia Dewi Juliawati; Lukman Makmur; Mariko Katajima (Institut Teknologi Bandung, 2005)
Sifat Listrik Film Tipis SrTiO3 untuk Kapasitor MOS An anti-tumor calcon has been isolated from Criptocarya costata stem bark. The compound was obtained from chloroform fraction fractioned by chromatography technique and recrystalized in n-hexane and ethyl acetate. The compound structure elucidated based on physical and spectroscopic data was 2,4-dihydroxy-3,5,6-trimethoxy calcon. Cytotoxic assay using murine leukemia cell P388 showed positive activity with IC50 value of 3.65 Âµg/mL.